POSSIBILITIES OF DYNAMIC BIOMETRICS FOR AUTHENTICATION AND THE CIRCUMSTANCES FOR USING DYNAMIC BIOMETRIC SIGNATURE - Hortai, František (Moravská vysoká škola Olomouc, 2017)
New information technologies alongside their benefits also bring new dangers with themselves. It is difficult to decide which authentication tool to use and implement in the information systems and electronic documents. The final decision has to compromise among the facts that it faces several conflicting requirements: highly secure tool, to be a user-friendly and user simplicity method, ensure protection against errors and failures of users, speed of authentication and provide these features for a reasonable price. Even when the compromised solution is found it has to fulfill the given technology standards. For the listed reasons the paper argues one of the most natural biometric authentication method the dynamic biometric signature and lists its related standards. The paper also includes measurement evaluation which solves the independence between the person’s signature and device on which it was created.

New information technologies alongside their benefits also bring new dangers with themselves. It is difficult to decide which authentication tool to use and implement in the information systems and electronic documents. The final decision has to compromise among the facts that it faces several conflicting requirements: highly secure tool, to be a user-friendly and user simplicity method, ensure protection against errors and failures of users, speed of authentication and provide these features for a reasonable price. Even when the compromised solution is found it has to fulfill the given technology standards. For the listed reasons the paper argues one of the most natural biometric authentication method the dynamic biometric signature and lists its related standards. The paper also includes measurement evaluation which solves the independence between the person’s signature and device on which it was created.
POSSIBILITIES OF DYNAMIC BIOMETRICS FOR AUTHENTICATION AND THE CIRCUMSTANCES FOR USING DYNAMIC BIOMETRIC SIGNATURE
Keywords: Authentication; dynamic biometrics; dynamic biometric signature; information system security; biometric standards.; Authentication; dynamic biometrics; dynamic biometric signature; information system security; biometric standards.